The Implementation of the Apostle Paul’s Exhortation on the Call to Ministry Based on 2 Timothy 2:1–13 among Servants of Christ - Awang; Sri Wahyun Wahyuni; Yonatan Purnomo (ORTHOTOMEO : Jurnal Penelitian Ilmiah, 2025)
The call to ministry is an essential aspect of the life of a servant of Christ, requiring perseverance, faithfulness, and sacrifice. In 2 Timothy 2:1–13, the Apostle Paul exhorts Timothy to carry out ministry through the strength of Christ’s grace, illustrated by the metaphors of a soldier, an athlete, and a farmer. This study aims to analyze the level of implementation of Paul’s exhortation regarding the call to ministry and to identify the most dominant dimension shaping ministerial practice among servants of Christ at the Kemah Injil Indonesia Hosana Tumbang Kubang Church, Seruyan Hulu, Central Kalimantan. This research employs a quantitative approach using a survey method involving 33 respondents from the church’s governing body. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, normality testing, confidence interval analysis, and linear regression with the assistance of SPSS 25. The findings indicate that the implementation of Paul’s exhortation is at a moderate level. Among the three examined dimensions, working hard like a farmer (D3) emerges as the most dominant factor influencing the implementation of the call to ministry, with a correlation coefficient of 0.911 and a contribution of 83%. These results emphasize that perseverance and consistent diligence in ministry are fundamental to faithfully and sustainably living out the call to serve.